Book review: Aditya Nigam, Decolonizing Theory: Thinking across Traditions. (July 2021) - Pramanik, Avijit
Aditya Nigam, Decolonizing Theory: Thinking across Traditions (New Delhi: Bloomsbury, 2020), xxv + 320 pp.